The Entremesil Production of José Julián López de Castro (Castilla. Estudios de Literatura, 2019)
José Julián López de Castro is an 18th century writer born in Madrid who, despite of having a significant literary work, has gone practically unnoticed to this day. He mainly concentrated on poetry and theatre, which he maintained a close relation with, due to his membership of an important family of actors. Its dramatic production, specially his interludes (entremeses), will be the object of study of this article. The literary heritage is latent in his short pieces perfectly combined with 18th century elements, so that in his works the past and the present, the tradition and the modernity, the old and the current come together.
Keywords: López de Castro; 18th century; theatrical genre; interludes (entremeses); literary tradition